Knowledge in the dark: scientific challenges and ways forward - Jonathan M. Jeschke; Sophie Lokatis; Isabelle Bartram; Klement Tockner (Canadian Science Publishing, 2019)
A key dimension of our current era is Big Data, the rapid rise in produced data and information; a key frustration is that we are nonetheless living in an age of ignorance, as the real knowledge and understanding of people does not seem to be substantially increasing. This development has critical consequences, for example it limits the ability to find and apply effective solutions to pressing environmental and socioeconomic challenges. Here, we propose the concept of "knowledge in the dark"-or short: dark knowledge-and outline how it can help clarify key reasons for this development: (i) production of biased, erroneous, or fabricated data and information; (ii) inaccessibility and (iii) incomprehensibility of data and information; and (iv) loss of previous knowledge. Even in the academic realm, where financial interests are less pronounced than in the private sector, several factors lead to dark knowledge, that is they inhibit a more substantial increase in knowledge and understanding. We highlight four of these factors-loss of academic freedom, research biases, lack of reproducibility, and the Scientific tower of Babel-and offer ways to tackle them, for example establishing an international court of arbitration for research and developing advanced tools for research synthesis.